2022
DOI: 10.1101/2022.02.06.479275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Taxonomic practice, creativity, and fashion: What’s in a spider name?

Abstract: There is a secret pleasure in naming new species. Besides traditional etymologies recalling the sampling locality, habitat, or morphology of the species, etymologies may be tributes to some meaningful person (for example, the species collector, the author husband or wife, or a celebrity), pop culture references, and even exercises of enigmatography. The possibility of choosing witty or even playful names for new species departs from the otherwise impersonal and old-fashioned writing style that is common in tax… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The frequency distribution of the lengths of species epithets among spiders is strikingly similar to ours, with the same shape and mode, resulting in practically the same average length. In addition, there was no temporal change in the average length of species epithets among spiders, even though the spider data set spanned more than two centuries (Mammola et al 2022), whereas ours covered just over two decades. It seems therefore that the few patterns we observed are not unique to parasite species, but may reflect broader practices in taxonomy.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The frequency distribution of the lengths of species epithets among spiders is strikingly similar to ours, with the same shape and mode, resulting in practically the same average length. In addition, there was no temporal change in the average length of species epithets among spiders, even though the spider data set spanned more than two centuries (Mammola et al 2022), whereas ours covered just over two decades. It seems therefore that the few patterns we observed are not unique to parasite species, but may reflect broader practices in taxonomy.…”
Section: Discussionmentioning
confidence: 79%
“…The only comparable study we are aware of is an investigation of the names of over 48,000 spider species described since the middle of the 18 th century (Mammola et al 2022 ). The frequency distribution of the lengths of species epithets among spiders is strikingly similar to ours, with the same shape and mode, resulting in practically the same average length.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a tendency, significant but weak, for names based on host plants to have become less common over time. Mammola et al (2022) found a similar but stronger effect for ecologically informative names among spiders, although Poulin et al (2022) found no such trend for parasitic worms. These patterns underscore the fundamentally creative nature of the naming act.…”
Section: Discussionmentioning
confidence: 92%
“…Mammola et al . [5] found a similar but stronger effect for ecologically informative names among spiders, although Poulin et al . [6] found no such trend for parasitic worms.…”
Section: Discussionmentioning
confidence: 98%
“…We also found a tendency, significant but weak, for names based on host plants to have become less common over time. Mammola et al [5] found a similar but stronger effect for ecologically informative names among spiders, although Poulin et al [6] found no such trend for parasitic worms. These patterns underscore the fundamentally creative nature of the naming act.…”
Section: Discussionmentioning
confidence: 99%